The Influence of the Independent Curriculum on the Learning Motivation of SMA Negeri 1 Pematang Siantar Students - Situmorang, Anggi Natalia; Parhusip, Doelce Theresia; Simanjuntak, Emy Sulastri; Simanjuntak, Daniel; Hutabarat, Ricky Paulus; Sibagariang, Susy Alestriani (Journal of English Language and Education, 2026)
Education is a systematic process in helping individuals develop their potential, where the Independent Curriculum presents as an innovation that emphasizes flexibility and student-centered learning. This study aims to understand in depth how the implementation of the Independent Curriculum affects student learning motivation at SMA Negeri 1 Pematang Siantar. This study used a qualitative approach with a descriptive study method and in-depth interviews with ten students in grades 10 and 11 selected using a purposive sampling technique. In addition to interviews, data collection techniques also involved participant observation and documentation to explore the subjects' experiences comprehensively. The results show that the Independent Curriculum has a positive impact on student learning motivation, where students feel more enthusiastic and responsible because they have the freedom to choose activities that suit their interests. The collaborative and project-based learning environment has been shown to foster intrinsic motivation and self-confidence. In conclusion, this study provides a theoretical contribution to the development of the concept of learning motivation in the context of Indonesian education and serves as a practical reference for teachers and schools that the Independent Curriculum is effective in increasing motivation by fulfilling psychological needs for autonomy, competence, and social connectedness.